UPAYA PENINGKATAN KEAKTIFAN SISWA MELALUI METODE PEMBELAJARAN TANYA JAWAB DI SMPS MAZUMA AGRO INDONESIA - Anggraini, Maya Dita (Sindoro: Cendikia Pendidikan, 2024)
Basically, the level of educational quality of a region or group can be measured from the Human Resources contained therein. In an effort to improve the quality of education, students must contribute actively to learning. Meanwhile, increasing student activity in learning is the teacher's task as a determinant of learning strategies and methods. The question and answer learning method is considered effective in stimulating student activity. This research method is descriptive qualitative, with a case study type of research. This research data is based on observations of class IX students at SMPS Mazuma Agro Indonesia as research subjects. Efforts to increase students' understanding through the question and answer learning method were successful with various variations, namely questions and answers between teachers and students orally, in writing, and questions and answers between students through group discussions. Pada dasarnya, tingkat kualitas pendidikan suatu daerah atau kelompok, dapat diukur dari Sumber Daya Manusia yang terdapat didalamnya. Dalam upaya meningkatkan kualitas pendidikan, maka siswa harus berkontribusi secara aktif dalam pembelajaran. Sedangkan meningkatkan keaktifan siswa dalam pembelajaran menjadi tugas guru sebagai penentu strategi dan metode pembelajaran. Metode pembelajaran tanya jawab dinilai efektif dalam memacu keaktifan siswa. Metode penelitian ini berupa kualitatif deskrptif, dengan jenis penelitian studi kasus. Data penelitian ini berdasarkan observasi terhadap siswa kelas IX SMPS Mazuma Agro Indonesia sebagai subjek penelitian. Upaya peningkatan pemahaman siswa melaui metode pembelajaran tanya jawab berhasil dengan berbagai variasi yang dilakukan, yaitu tanya jawab antara guru dengan siswa secara lisan, tertulis, dan tanya jawab antar siswa melalui diskusi kelompok.